Odpowiedź :
Obliczenia
[tex]\frac{3^6\cdot(3^2)^3}{9^2\cdot3^7}=\frac{3^6\cdot3^{2\cdot3}}{(3^2)^2\cdot3^7}=\frac{3^6\cdot3^6}{3^{2\cdot2}\cdot3^7}=\frac{3^{6+6}}{3^4\cdot3^7}=\frac{3^{12}}{3^{4+7}}=\frac{3^{12}}{3^{11}}=3^{12-11}=3^1=\boxed3\\\\\text{Gotowe!}[/tex]
Wykorzystane wzory
[tex]a^m\cdot a^n=a^{m+n}\\\\a^m:a^n=a^{m-n}\\\\(a^m)^n=a^{m\cdot n}[/tex]
Wyjaśnienie :
3^6 · (3²)³ / 9² · 3^7 =
1. 3^6 · (3²)³ = 3^6 · 9³ = 729 · 729 = 531441
2. 9² · 3^7 = 81 · 2187 = 177147
3. 531441 : 177147 = 3
Odp : Wynik to 3
Mam nadzieje, że pomogłem :)